2019
DOI: 10.1097/scs.0000000000005103
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nasal Alterations in Le Fort I Advancement: Linear Measurements, Angles, Nasal Indices, and Volume Differences

Abstract: The maxillary advancement obtained by the Le Fort I osteotomy can also generate significant changes in the soft tissue of the nose and lips. The aim of this study was to compare the alterations in the soft tissue of the nose following the Le Fort I osteotomy maxillary advancement technique in a population of young adults submitted to orthognathic surgery. Seven men and 8 women aged between 23 and 45 underwent orthognathic surgery using the Le Fort I osteotomy and bilateral mandibular sagittal osteotomy. Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Many studies reported that the amount of maxillary movement affects these parameters, and these parameters were mainly analyzed from profile and frontal views. 4,8,13 Although the bottom view is not always seen during social interaction, the head's movement while smiling, drinking, or eating makes this view visible. With selfie photography by smartphones and social media taking their place in our daily lives, the bottom view of the nose has gained importance for evaluating the nose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies reported that the amount of maxillary movement affects these parameters, and these parameters were mainly analyzed from profile and frontal views. 4,8,13 Although the bottom view is not always seen during social interaction, the head's movement while smiling, drinking, or eating makes this view visible. With selfie photography by smartphones and social media taking their place in our daily lives, the bottom view of the nose has gained importance for evaluating the nose.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many parameters such as alar width, alar base width, nostril shape, and columella length related to inferior nasal area aesthetic. Many studies reported that the amount of maxillary movement affects these parameters, and these parameters were mainly analyzed from profile and frontal views 4,8,13. Although the bottom view is not always seen during social interaction, the head’s movement while smiling, drinking, or eating makes this view visible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] In the literature, there have been many studies about impact of skeletal changes on nasal region following maxillary surgery and these studies mainly focused on parameters such as nasal tip, paranasal soft tissue projection, and alar width. [5][6][7][8][9] Results of these studies contribute to make an algorithm between hard tissue and soft tissue projection for virtual 3D computer aided planning systems for orthognathic surgery. Virtual surgical planning and rapid prototyping technology provide new possibilities for a comprehensive 3D evaluation of dental arches and skeletal structures to simulate different surgical plans and predict relevant outcomes.…”
mentioning
confidence: 99%